2017
DOI: 10.1089/jwh.2016.6044
|View full text |Cite
|
Sign up to set email alerts
|

Speaker Introductions at Internal Medicine Grand Rounds: Forms of Address Reveal Gender Bias

Abstract: In this study, women introduced by men at IMGR were less likely to be addressed by professional title than were men introduced by men. Differential formality in speaker introductions may amplify isolation, marginalization, and professional discomfiture expressed by women faculty in academic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
163
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(166 citation statements)
references
References 34 publications
0
163
2
1
Order By: Relevance
“…In a recent observational study of video‐archived speaker introductions at internal medicine grand rounds, women were less likely to be introduced by professional title than their male counterparts if the introductory speaker was a man (49.2% for women vs 72.4% for men). When the introducer was a female, both men and women were similarly introduced by professional title (97.8% female vs 95.0% male) …”
Section: Barriers Facing Women In Cardiologymentioning
confidence: 99%
“…In a recent observational study of video‐archived speaker introductions at internal medicine grand rounds, women were less likely to be introduced by professional title than their male counterparts if the introductory speaker was a man (49.2% for women vs 72.4% for men). When the introducer was a female, both men and women were similarly introduced by professional title (97.8% female vs 95.0% male) …”
Section: Barriers Facing Women In Cardiologymentioning
confidence: 99%
“…However, there is ample evidence of persistent gender discrimination against women physicians, from disrespectful treatment to persistent pay discrepancies that are evident among early and mid-career academic physicians as well as those in private practice 45678. When directly asked, 70-77% of women physicians report experiencing gender discrimination,910 and 30% of academic women physicians report having experienced sexual harassment 9.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an analysis of 321 grand round introductions identified that when a man introduced a speaker, they included the professional title 72.4% of the time for male speakers versus 49.2% for female speakers 35. In comparison, women included the professional title for 95.0% of male speakers and 97.8% of female speakers 35. These actions illustrate, and reinforce, an unconscious bias against women in professional practice.…”
Section: Discussionmentioning
confidence: 97%
“…Physicians (attendings and other residents) are more likely to disregard the credentials of female residents when introducing the resident to a patient (female 56% vs male 8%; p<0.001), while patients display a similar but more profound disregard of female residents’ credentials (female 79% vs male 12%; p<0.001) 24. Similarly, an analysis of 321 grand round introductions identified that when a man introduced a speaker, they included the professional title 72.4% of the time for male speakers versus 49.2% for female speakers 35. In comparison, women included the professional title for 95.0% of male speakers and 97.8% of female speakers 35.…”
Section: Discussionmentioning
confidence: 99%